CULTURE AND GENDER REPRESENTATION IN VISUAL AND VERBAL TEXTS: AN ANALYSIS OF NATIONALLY ENDORSED INDONESIAN EFL TEXTBOOKS FOR UPPER SECONDARY STUDENTS - Lelyana Syarif; Herri Mulyono (International Journal of Educational Best Practices, 2023)
This study aimed to analyze the representation of culture and gender in visual and verbal texts in English as a Foreign Language (EFL) textbooks used by upper secondary school students. A content analysis was conducted on three EFL textbooks for upper secondary school students, using Xiao's (2010) framework to guide the analysis of culture “small-c”representation, and Brugeilles and Cromer's (2009) study to examine gender character according to their roles portrayed in the textbooks. The findings revealed that the highest number of visual illustrations was predominantly presented in the lifestyle aspect, followed by customs, values, holidays, hobbies, and food. It was also observed that gender representation was equally represented in the verbal text, but not proportionally in the visuals. The findings indicate that culture and gender awareness among students could be improved if textbooks provided a more balanced representation of various cultures encompassing source culture, target culture, and international target culture, and paid more attention to the equal treatment of genders.